2016
DOI: 10.11113/umran2016.3n3-1.147
|View full text |Cite
|
Sign up to set email alerts
|

Science Education Based on Cirebon Local Culinary Food

Abstract: Cirebon is an area that has rich culture, including culinary. Science education or at school is known as the Natural Sciences (IPA), is expected to integrate the cultural heritage of culinary in Cirebon without compromising the activity of science process containaed in it. The process of science in learning the concept of food and nutrition at schools can be done by observing Cirebon local foods available in the students’ neighborhood. The Nutrient content of Cirebon local foods such as sega jamblang, empal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Ethnic-based science learning guides students in finding and building their knowledge (Hairida, 2017;Hartini et al, 2018). Furthermore, learning based on local wisdom produces more meaningful learning because the objects observed are in the environment (Susilawati et al, 2016).…”
Section: Figure 1 Critical Thinking Skills Indicatormentioning
confidence: 99%
“…Ethnic-based science learning guides students in finding and building their knowledge (Hairida, 2017;Hartini et al, 2018). Furthermore, learning based on local wisdom produces more meaningful learning because the objects observed are in the environment (Susilawati et al, 2016).…”
Section: Figure 1 Critical Thinking Skills Indicatormentioning
confidence: 99%
“…Ethnosciencebased science learning guides students in finding and building their own knowledge (Rahayu & Sudarmin, 2015). Moreover, the local wisdombased learning results in a more meaningful learning since the observed object exists in the environment (Susilawati et al, 2016).…”
Section: The Effectiveness Of the Physics Teaching Materialsmentioning
confidence: 99%
“…Empiric evidence and previous research showed the development of local wisdom in Indonesia include local wisdom in elementary schools (Andriana et al, 2017); junior high schools (Suastra, 2010;Suastra et al, 2011;Damayanti et al, 2013;Khusniati, 2014;Andriana et al, 2017;Dwianto et al, 2017;Kurniawati et al, 2017;Suastra, 2017;Septiani, 2020); senior high schools (Suastra, 2013;Ardan et al, 2015;Hidyanto et al, 2016;Suastra et al, 2017;Hartini et al, 2018); higher education and society (Meliono, 2011;Ardan et al, 2015;Atmojo, 2015;Parmin et al, 2015;Rusilowati et al, 2015;Ratana-Ubol, 2016;Susilawati et al, 2016;Setiawan et al, 2017;Toharudin & Kurniawan, 2017;Atmojo et al, 2018;Septiani, 2020).…”
Section: Introductionmentioning
confidence: 99%